Growth and anabolic hormones, leptin, and neuromuscular performance in moderately trained prepubescent athletes and untrained boys - Tsolakis, C.; Vagenas, G.; Dessypris, A. (The Journal of Strength and Conditioning Research, 2003)
We investigated hormonal regulators of growth and development, leptin levels, body composition, neuromuscular performance, and the associations among them in trained prepubertal athletes (experimental group [EG]) and an untrained control group (CG). Informed consent was obtained from the children and their parents. Their maturation stage was evaluated according to Tanner's criteria. There were no differences between EG and CG in physical characteristics, body mass index (BMI), lean body mass, testosterone (T), sex hormone-binding globulin, free androgen index, growth hormone (GH), hand grip strength, and jumping performance. Leptin levels and percent fat of the EG were significantly lower than those of the CG (p < 0.05-0.005). Leptin levels were significantly correlated to body fat and BMI for both the EG and the CG (r = 0.51-0.79). There is little evidence that leptin has a positive effect on growth and anabolic factors. Sex hormone-binding globulin and GH may explain the variation of leptin in athletes with low T (R2 = 0.43) and in CG (R2 = 0.35), respectively. Leptin seems to be a permissive factor for the onset of puberty, and the training background needs an optimal biological maturation to produce significant differences in muscle and power performance.